Development and detection application of monoclonal antibodies against Zucchini yellow mosaic virus - Zhe CHEN; Ming-hao ZHANG; Xue-ping ZHOU; Jian-xiang WU (Journal of Integrative Agriculture, 2017)
Aphid-borne Zucchini yellow mosaic virus (ZYMV) is one of the most economically important viruses of cucurbitaceous plants. To survey and control this virus, it is necessary to develop an efficient detection technique. Using purified ZYMV virion and the conventional hybridoma technology, three hybridoma cell lines (16A11, 5A7 and 3B8) secreting monoclonal antibodies (MAbs) against ZYMV Zhejiang isolate were obtained. The working titers of the ascitic fluids secreted by the three hybridoma cell lines were up to 10−7 by indirect enzyme-linked immunosorbent assay (ELISA). All MAbs were isotyped as IgG1, kappa light chain. Western blot analysis indicated that the MAb 3B8 could specifically react with the coat protein of ZYMV while MAbs 5A7 and 16A11 reacted strongly with a protein of approximately 51 kDa from the ZYMV-infected leaf tissues. According to this molecular weight, we consider this reactive protein is likely to be the HC-Pro protein. Using these three MAbs, we have now developed five detection assays, i.e., antigen-coated-plate ELISA (ACP-ELISA), dot-ELISA, tissue blot-ELISA, double-antibody sandwich ELISA (DAS-ELISA), and immunocapture-RT-PCR (IC-RT-PCR), for the sensitive, specific, and easy detection of ZYMV. The sensitivity test revealed that ZYMV could be readily detected respectively by ACP-ELISA, dot-ELISA, DAS-ELISA and IC-RT-PCR in 1:163 840, 1:2 560, 1:327 680 and 1:1 310 720 (w/v, g mL−1) diluted crude extracts from the ZYMV-infected plants. We demonstrated in this study that the dot-ELISA could also be used to detect ZYMV in individual viruliferous aphids. A total of 275 cucurbitaceous plant samples collected from the Zhejiang, Jiangsu, Shandong and Hainan provinces, China, were screened for the presence of ZYMV with the described assays. Our results showed that 163 of the 275 samples (59%) were infected with ZYMV. This finding indicates that ZYMV is now widely present in cucurbitaceous crops in China. RT-PCR followed by DNA sequencing and sequence analyses confirmed the accuracy of the five assays. We consider that these detection assays can significantly benefit the control of ZYMV in China.